2009
DOI: 10.1063/1.3216573
|View full text |Cite
|
Sign up to set email alerts
|

Coarse grained simulations of a small peptide: Effects of finite damping and hydrodynamic interactions

Abstract: In the coarse grained Brownian Dynamics simulation method the many solvent molecules are replaced by random thermal kicks and an effective friction acting on the particles of interest. For Brownian Dynamics the friction has to be so strong that the particles' velocities are damped much faster than the duration of an integration timestep. Here we show that this conceptual limit can be dropped with an analytic integration of the equations of damped motion. In the resulting Langevin integration scheme our recentl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…All simulations were performed using software written in-house and using the Langevin dynamics algorithm developed as an extension of the Ermak-McCammon algorithm by the Geyer group69. Simulations were performed at 310K, with the solvent dielectric constant and viscosity set to the corresponding experimental values for water.…”
Section: Methodsmentioning
confidence: 99%
“…All simulations were performed using software written in-house and using the Langevin dynamics algorithm developed as an extension of the Ermak-McCammon algorithm by the Geyer group69. Simulations were performed at 310K, with the solvent dielectric constant and viscosity set to the corresponding experimental values for water.…”
Section: Methodsmentioning
confidence: 99%
“…If so, a recent advance made by Geyer & Winter is likely to be extremely important: in highly original work [74• •], this group has shown that an approximate factorization of the diffusion tensor (which is norm ally achieved by a computationally nightmarish Cholesky decomposition) can capture ~95% of the HI effect at a fraction of the computational cost. This advance, together with a subsequent extension of the thinking to a Langevin dynamics setting [75], may provide something of a revolution in the scale over which hydrodynamic effects are modeled in concentrated protein system s.…”
Section: The Status Of the Fieldmentioning
confidence: 99%
“…Second, intermolecular interactions can be modeled as the interaction of fixed interaction sites on one solute with a precomputed interaction potential grid on another solute, reducing the formal scaling of the calculation of intermolecular forces to O ( N ), with N the number of solute atoms, compared to the O(N2) or O(N ln N) algorithms in MD. This treatment of forces between solutes is used in simulation of diffusional association (SDA) and is also employed in other BD simulation software packages, namely, UHBD, Browndye, BrownMove, and Macrodox …”
Section: Introductionmentioning
confidence: 99%